CONSISTENT CONDOM USE DETERMINANTS AMONG WOMAN THAT HAVE VAGINAL, ORAL AND ANAL SEX - Robles Montijo, Susana; Piña López, Julio Alfonso; Moreno Rodríguez, Diana (Anales de Psicología / Annals of Psychology, 2006)
Some variables from the psychological prevention model ap-plied to AIDS were examined as predictors of consistent condom use during vaginal, oral and anal sex among university woman. A cross-sectional correlational design was used with a sample of 355 university female students’ age 18 to 26 years from a public school of Mexico State. Anonymous self-report questionnaires were used to collect the data and include the evaluation of knowledge, self-efficacy and attitudes about HIV/AIDS, and also three situational variables: to investigate the partner’s sexual his-tory during vaginal, oral and anal sex. Consistent condom use during vaginal, oral and anal sex was measured trough the proportion of unprotected sexual intercourse in the last three months. Logistic regression analysis evaluated the influence of model variables on each risk behavior. The predictive model of condom use consisted of only tow variables that refers motivational and situational issues of each risk behavior. The data are discussed in the context of model applied to AIDS emphasizing the role of motivational and situational factors and the importance of the development of functional competences in woman.